STRATEGI MANAJEMEN PAMERAN VIRTUAL SENI LUKIS DALAM MEMBANGUN PENGALAMAN INTERAKTIF BAGI SISWA KELAS XII MIPA 4 SMAN 3 SEMARANG - Anggun Mega; Hartono (Universitas Pendidikan Ganesha, 2024)
In the increasingly developing digital era, one form of artistic expression that is undergoing transformation through the application of technology is art exhibitions. In its development, exhibitions can be held virtually. This research aims to (1) explain the management strategy for virtual painting exhibitions in building interactive experiences for class XII students at SMA Negeri 3 Semarang, (2) explain the implementation of virtual exhibitions for class XII students at SMA Negeri 3 Semarang, (3) explain the impact The use of virtual painting exhibitions for the learning of class XII students at SMA Negeri 3 Semarang. This research uses a qualitative method that produces data in the form of descriptive narratives and phenomenology is determined as a methodological approach that aims to discuss subjective experience as a whole. Data collection techniques use interviews, observation and documentation. Before the data is analyzed, the validity of the data is carried out first through triangulation of sources and theories. Next, the data is analyzed using interactive data analysis with the flow of data reduction, data display, and conclusion: verification. Based on the research results, it can be concluded that the virtual management strategy for painting in class XII MIPA 4 students at SMA Negeri 3 Semarang goes through the stages of planning, organizing, moving and supervising in the digital space. Implementing a virtual painting exhibition can provide an interactive experience for students in a different environment. The impact of using a virtual painting exhibition for students is (1) an in-depth learning experience; (2) development of visual and aesthetic skills; (3) stimulation of creativity; (4) interactive and participatory learning; (5) development of technological skills; (6) increasing appreciation for art. Keywords : Management, exhibition, virtual, interactive. Abstrak Dalam era digital yang semakin berkembang, salah satu bentuk ekspresi seni yang mengalami transformasi melalui penerapan teknologi adalah pameran seni. Dalam perkembangannya pameran dapat dilakukan secara virtual. Penelitian ini bertujuan untuk (1) menjelaskan strategi manajemen pameran virtual seni lukis dalam membangun pengalaman interaktif bagi siswa kelas XII di SMA Negeri 3 Semarang, (2) menjelaskan implementasi pameran virtual bagi siswa kelas XII di SMA Negeri 3 Semarang, (3) menjelaskan dampak penggunaan pameran virtual seni lukis terhadap pembelajaran siswa kelas XII di SMA Negeri 3 Semarang. Penelitian ini menggunakan metode kualitatif yang menghasilkan data berupa narasi deskriptif dan fenomenologi ditetapkan sebagai pendekatan metodologi yang bertujuan membahas pengalaman subjektif secara keseluruhan. Teknik pengumpulan data menggunakan wawancara, observasi dan dokumentasi. Sebelum data dianalisis, dilakukan keabsahan data terlebih dahulu dengan melalui triangulasi sumber dan teori. Kemudian data dianalisis menggunakan analis data interaktif dengan alur data reduction, data display, dan conclusion: verification. Berdasarkan hasil penelitian dapat disimpulkan bahwa startegi manajemen virtual seni lukis siswa kelas XII MIPA 4 di SMA Negeri 3 Semarang melalui tahapan merencanakan, mengorganisir, menggerakan, dan melalukan pengawasan dalam ruang digital. Implementasi pameran virtual seni lukis dapat memberikan pengalaman interaktif bagi siswa di dalam lingkungan yang berbeda. Dampak penggunaan pameran virtual seni lukis bagi siswa adalah (1) pengalaman belajar yang mendalam; (2) pengembangan keterampilan visual dan estetika; (3) stimulasi kreativitas; (4) pembelajaran interaktif dan partisipatif; (5) pengembangan keterampilan teknologi; (6) peningkatan apresiasi terhadap seni.